2014
DOI: 10.1162/jocn_a_00632
|View full text |Cite
|
Sign up to set email alerts
|

Music and Language Expertise Influence the Categorization of Speech and Musical Sounds: Behavioral and Electrophysiological Measurements

Abstract: In this study, we used high-density EEG to evaluate whether speech and music expertise has an influence on the categorization of expertise-related and unrelated sounds. With this purpose in mind, we compared the categorization of speech, music, and neutral sounds between professional musicians, simultaneous interpreters (SIs), and controls in response to morphed speech-noise, music-noise, and speech-music continua. Our hypothesis was that music and language expertise will strengthen the memory representations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(22 citation statements)
references
References 70 publications
(100 reference statements)
0
22
0
Order By: Relevance
“…Yet the bilingual experience seems to exert distinctive and far-reaching influences on cognition. For example, in addition to its differential effects on executive performance (Bialystok and DePape, 2009), the acquisition of expert bilingual skills seems to modulate processing of non-verbal information from other specific domains, such as musical items (Elmer et al, 2014).…”
Section: Bilingualism As a Source Of Cognitive Reserve In Ad Patientsmentioning
confidence: 99%
“…Yet the bilingual experience seems to exert distinctive and far-reaching influences on cognition. For example, in addition to its differential effects on executive performance (Bialystok and DePape, 2009), the acquisition of expert bilingual skills seems to modulate processing of non-verbal information from other specific domains, such as musical items (Elmer et al, 2014).…”
Section: Bilingualism As a Source Of Cognitive Reserve In Ad Patientsmentioning
confidence: 99%
“…Moreover, it has been shown that music training also enhances several aspects of language processing, including phoneme and syllable perception (Musacchia et al, 2007; Chobert et al, 2011, 2014; Marie et al, 2011; Elmer et al, 2012, 2014; Parbery-Clark et al, 2012; Kühnis et al, 2013; Bidelman et al, 2014), the processing of pitch and prosody (Schön et al, 2004; Thompson et al, 2004; Delogu et al, 2006; Magne et al, 2006; Marques et al, 2007; Wong et al, 2007; Lima and Castro, 2011; Bidelman et al, 2013), phonological processing and reading (Anvari et al, 2002; Moreno et al, 2009; Corrigall and Trainor, 2011; Huss et al, 2011), speech segmentation (François et al, 2013), and syntactic processing (Jentschke and Koelsch, 2009; Gordon et al, 2015). However, it remains an open question whether music training improves associative learning and semantic memory, two of the processes that are at the heart of word learning but that are not necessarily language-specific (Markson and Bloom, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Such plastic changes can be found at the macroanatomical (Elmer, Hänggi, Meyer, & Jäncke, 2013;Bermudez, Lerch, Evans, & Zatorre, 2009;Schneider et al, 2005) as well as at the functional (Kühnis, Elmer, Meyer, & Jäncke, 2013b;Ellis et al, 2012;Elmer, Meyer, & Jäncke, 2012;Marie, Kujala, & Besson, 2012;Schneider et al, 2005) level and often correlate fairly well with the age of commencement of musical training (Pantev et al, 1998), the years of training (Musacchia, Sams, Skoe, & Kraus, 2007), or even with the cumulative hours of training (Elmer et al, 2012). Therefore, it is not really surprising that training-related changes in auditoryrelated brain regions of musicians strengthen the faculty to perceive or categorize musical sounds (Elmer, Klein, Kühnis, Liem, Meyer, & Jäncke, 2014;Meyer, Baumann, & Jäncke, 2006;Pantev, Roberts, Schulz, Engelien, & Ross, 2001) or even temporal and spectral (Kühnis, Elmer, Meyer, & Jäncke, 2013a;Kühnis et al, 2013b;Elmer et al, 2012;Marie et al, 2012;Marie, Delogu, Lampis, Belardinelli, & Besson, 2011;Marie, Magne, & Besson, 2011) speech information. However, from a methodological point of view, it is important to differentiate between active (i.e., discrimination or categorization) tasks and passive listening paradigms.…”
Section: Introductionmentioning
confidence: 99%